MENINGKATKAN PEMAHAMAN HADIST RIWAYAT MUSLIM DARI ABU. HURAIRAH DAN AKTIVITAS SISWA DALAM PEMBELAJARAN QURAN HADIST MELALUI PENDEKATAN COOPERATIVE LEARNING - Ali Musyafak (STIT Islamic Village Tangerang, 2023)
The purpose of writing this article is to describe the results of classroom action research on the application of Cooperative Learning in increasing students' understanding of the hadiths of Muslim history from Abu Huraira and students' activity. The hadith in question is about helping others. The research sample was students grade VIII of MTS N 1 Pati. Data collection uses observation method, learning achievement tests and questionnaires. Quantitative and qualitative data analysis techniques. The results showed that the application of Cooperative Learning can improve students' understanding of the hadiths of Muslim narrations from Abu Huraira and increase studens' activity in Al-Quran Hadith subjects